2012
DOI: 10.1136/sextrans-2012-050601a.11
|View full text |Cite
|
Sign up to set email alerts
|

O11 Health promotional messages in short message service (SMS) follow-up of GU medicine clinic defaulters; a tool to improve subsequent attendance rates?

Abstract: diverse towns in four Australian states (total population 72 000 16e29-year-olds). To date, 27 towns have been randomised (13 intervention, 14 control). Intervention and control towns are similar: baseline chlamydia prevalence (5.8%, 95% CI 4.4 to 7.5% vs 5%, 95% CI 3.9 to 6.3%, individual response rate 63%); past chlamydia testing rate in 16e29-year-olds (6.1%, 95% CI 5.8 to 6.4% vs 5.8%, 5.6 to 6%). After 3 months of the intervention in the first two towns the chlamydia testing rate was 10.9% (95% CI 10.1% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…In the study by Fairhurst and Sheikh, 64 only patients who failed to attend two or more appointments in preceding 12 months were included. Rutland et al 83 recorded a reduction in non-reattendance of 3.7%, while Fairhurst and Sheikh 64 demonstrated a reduction in the non-attendance rate of 5.3%. These rates appear fairly modest compared with some of those achieved in the general clinic population.…”
Section: Previous Patterns Of Non-attendancementioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Fairhurst and Sheikh, 64 only patients who failed to attend two or more appointments in preceding 12 months were included. Rutland et al 83 recorded a reduction in non-reattendance of 3.7%, while Fairhurst and Sheikh 64 demonstrated a reduction in the non-attendance rate of 5.3%. These rates appear fairly modest compared with some of those achieved in the general clinic population.…”
Section: Previous Patterns Of Non-attendancementioning
confidence: 99%
“…Perhaps the only trials that recognise a 'horses for courses' approach are the trials by Perron et al, 78 which used a progressive escalation procedure, and by Rutland et al, 83 which employed multiple complementary approaches. Car et al 43 identified one low-quality study that showed that mobile text message reminders with postal reminders, compared with postal reminders alone, improved rate of attendance at health-care appointments (RR 1.10, 95% CI 1.02 to 1.19).…”
Section: Findings From Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of "Reminder plus" interventions include SMS notification of appointment with a health promotional message or postal reminders with additional information about medical procedures and the importance of follow-up. 70,72 A Cochrane Review 40 of Table 4 Judgement on quality of included trials (not already covered in included reviews)…”
Section: Reminders Increase Attendance At Appointmentsmentioning
confidence: 99%
“…Rutland et al 70 To determine whether SMS follow-up of patients who DNA booked GUM appointments improves subsequent re-attendance rates and to assess the impact of inclusion of a health promotional message on re-attendance rates.…”
Section: Nilmentioning
confidence: 99%